Arabic Songs and Aural Linguistic Competence: Between Phonological Sensitivity and Verbal Aesthetics - Mafazatul Lutfiyah; Saefullah Azhari; Nurul Istiqomah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2026)
Arabic listening (maharah istima') remains one of the most challenging language skills for junior secondary students due to differences in learning readiness, limited engaging instructional media, and low classroom participation. This study aims to evaluate the effectiveness of differentiated learning using Arabic songs in improving the maharah istima' ability of eighth-grade students at MTs Taswirul Afkar Surabaya. The research employed a qualitative and Quantitative approach with action Research design involving 28 students and one Arabic language teacher. Data were collected over four months (February–May 2024) through participatory observation, in-depth interviews, document analysis, and group discussions. Differentiated learning was implemented through content, process, and product differentiation using Arabic songs such as Ummi, Madrasati, Qasidah Burdah, and Ana Muslim. The findings indicate substantial improvement in students' listening skills. The average score increased from 65.2 in the initial assessment to 78.4 after the first cycle, while the second cycle demonstrated an overall gain of 20.4 points (31.3%) compared with the baseline. Learning mastery improved from 32% to 64%, accompanied by high student enthusiasm (91%) and active participation (95%). This study contributes practical evidence that integrating differentiated learning with Arabic songs provides an effective, enjoyable, and inclusive strategy for enhancing Arabic listening competence in Islamic junior secondary education